2016
DOI: 10.3892/ijmm.2016.2463
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Wnt/β-catenin signaling pathway in the response of chondrocytes to mechanical loading

Abstract: In order to better understand the mechanisms by which chondrocytes respond to mechanical stimulation, ATDC5 mouse embryonic carcinoma cells were induced to differentiate into chondrocytes and then exposed to mechanical loading. To specifically elucidate the role of this pathway, the localization and expression of proteins involved in the Wnt/β-catenin signaling pathway were observed. Chondrogenic-differentiated ATDC5 cells were exposed to a 12% cycle tension load for 1, 2, 4, or 8 h. At each time point, immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
2
16
0
Order By: Relevance
“…We analyzed β-catenin protein levels and cell localization after 3 h of HP, in agreement with a previous report suggesting that translocation of β-catenin is a rapid process [ 25 ]; in fact, Niu et al observed the pathway activation following loading, with a plateau of 2 h. Our HP induced a significant reduction of β-catenin protein levels, as analyzed by Western blot in OA chondrocytes; these results are supported by immunofluorescence microscopy images showing the reduction of β-catenin inside the nuclei and the increase of its cytoplasmic localization after HP exposure. These preliminary results suggest a possible role of the Wnt/β-catenin pathway in mediating mechanical stimuli to regulate chondrocytes’ activities.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We analyzed β-catenin protein levels and cell localization after 3 h of HP, in agreement with a previous report suggesting that translocation of β-catenin is a rapid process [ 25 ]; in fact, Niu et al observed the pathway activation following loading, with a plateau of 2 h. Our HP induced a significant reduction of β-catenin protein levels, as analyzed by Western blot in OA chondrocytes; these results are supported by immunofluorescence microscopy images showing the reduction of β-catenin inside the nuclei and the increase of its cytoplasmic localization after HP exposure. These preliminary results suggest a possible role of the Wnt/β-catenin pathway in mediating mechanical stimuli to regulate chondrocytes’ activities.…”
Section: Discussionsupporting
confidence: 77%
“…The biochemical and molecular mechanisms by which mechanical stress influences transcriptional activities in chondrocytes remain unclear. It has been reported that the Wnt/β-catenin pathway is associated with mechanical force application in joints, and that this signaling is activated after mechanical damage to cartilage [ 24 , 25 ].The Wnt/β-catenin pathway exerts a pivotal role in cartilage homeostasis and in OA pathogenesis [ 24 ]; in addition, it seems to be involved in the regulation of miRNA expression [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of Wnt signaling, by different stimuli, causes nuclear β-catenin translocation and initiates the transcription of many genes responsible for bone and cartilage turnover [60,61]. Protein levels of Wnt and β-catenin are increased in human OA chondrocytes; this abnormal signaling activation determines the up-regulation of MMPs and ADAMTS, the reduction of Col2a1, proteoglycans, and aggrecans expression, and induces apoptosis signaling, contributing to articular cartilage damage [15,[62][63][64][65][66]. Furthermore, it has been demonstrated the activation of Wnt/β-catenin pathway in articular cartilage of injured exercise-induced OA rat model [67], as well as the regulation of β-catenin mRNA and protein expression in in vitro chondrocytes subjected to intermittent cyclic mechanical tension and low HP [15,64,68,69].…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of low FSS, another risk factor for atherosclerosis, on Dvl2 are not yet fully understood. In osteoblast cells, the gene expression levels of Dvl2 and β- catenin are affected by mechanical stress ( 26 , 27 ). In the present study, detection of the gene and protein expression levels demonstrated the laminar FSS could inhibit the expression of Dvl2 and its localization to the basal body, whereas low FSS led to enhanced localization when loaded for 12–18 h. Therefore, in vascular ECs, external FSS could influence the expression and cellular localization of Dvl2.…”
Section: Discussionmentioning
confidence: 99%